Polarized pluralistic model: Characteristics of Nepalese press - K.C., Bhuwan (Bodhi: An Interdisciplinary Journal, 2019)
This paper presents a comparative study of Media System in the context of Nepal on the basis of Hallin and Mancini’s study. The paper shows that the characteristic of Nepalese press match with the polarized pluralistic model, which is prevailed in Southern European states. This study also helps to understand the effect of political parallelism in professionalism of Nepalese press.